ADVERSE CHILDHOOD EXPERIENCE DAN DELIBERATE SELF HARM PADA REMAJA DI INDONESIA - Anindya Dewi Paramita; Andi Tenri Faradiba; Khintan Sucitasari Mustofa (UIN Sunan Kalijaga, 2021)
Self-injurious behavior or acts of self-harm that are commonly found in adolescents are form of channeling negative emotions to deal with emotional pain. One reason for this pain was exposure to unpleasant experiences called adverse childhood experiences. This study aims to explore the detrimental effect of experience on self-harm in adolescents. This study used two measuring instruments, the Deliberate Self-Harm Inventory (DSHI) was used to measure DSH and Adverse Childhood Experience Quesionnaire (ACE.Q) was used to measure ACE. There were 168 respondents in the study who participated filling online questionnaire and they were gathered through non-probability sampling technique. The result showed that there was a positive correlation between adverse childhood experiences on self-harm with a sig value of 0.035 <0.05. This means that the higher the ACE, the higher the DSH. Perilaku melukai diri sendiri atau deliberate self-harm (DSH) banyak ditemukan pada remaja sebagai bentuk penyaluran emosi secara negatif untuk mengatasi rasa sakit secara emosional. Salah satu penyebab rasa sakit tersebut adalah adanya paparan pengalaman tidak menyenangkan yang disebut dengan adverse childhood experience (ACE). Penelitian ini bertujuan untuk mengetahui pengaruh adverse childhood experience terhadap deliberate self-harm pada remaja di Indonesia. Penelitian ini menggunakan dua alat ukur, yaitu Deliberate Self-Harm Inventory (DSHI) untuk mengukur DSH dan Adverse Childhood Experience Quesionnaire (ACE.Q) untuk mengukur ACE. Terdapat 168 responden dalam penelitian ini yang diperoleh secara online melalui teknik non-probability sampling. Hasil penelitian menunjukkan bahwa terdapat korelasi positif antara adverse childhood experience terhadap deliberate self-harm dengan nilai sig 0,035 < 0,05. Artinya, semakin tinggi adverse childhood experience maka semakin tinggi pula kecenderungan melakukan deliberate self-harm